PKM PEMANFAATAN BUAH NIPAH DI DESA TELUK BETUNG, KECAMATAN PULAU RIMAU, KABUPATEN BANYUASIN, SUMATERA SELATAN - Mukti, Retno Cahya; Arsi, Arsi; Pangawikan, Aldila Din (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2020)
The Community Partnership Program (PKM) activity aims to help groups of farmers from the community who are not yet economically productive but have a strong desire to become entrepreneurs. This PKM activity will be applied to farmer groups in Hamlet 4, Teluk Betung Village, Rimau Island District, Banyuasin District, South Sumatra. The obstacle faced by partners is that it is difficult to determine the right processing technique for nipah (Nypa fruticans Wurmb), partner's knowledge of nipah processing techniques is still minimal. From the problems faced by partners, several solutions are needed including providing community group empowerment assistance regarding the application of science and technology in activities: 1) knowledge of plants and the benefits of nipah (Nypa fruticans); 2) application of local resource-based food processing technology which includes selection of palm fruit, types, and processing techniques of fresh palm fruit; and 3) processing of nipah to be processed foodstuffs with high economic value such as sweets, dodol, etc., and 4) the production process and marketing management of processed nipah products. This activity will be carried out for 8 months (January to August) in 2019. The method used is the empowerment of active participant of farmer groups to partners with the transfer of knowledge and technology on the introduction and benefits of palm fruit, processing of palm fruit through direct assistance in the field. The process of delivering material utilizes teaching aids and the use of space as a transfer class of science and technology. While the technical assistance and direction of the service program involved partner groups. The conclusion is that partners are able to increase their knowledge and skills in processing nipah so that they can increase their economic value.